Konseling Islami untuk Mengatasi Percintaan yang Berlebihan: Pendekatan Qur’ani - Adzima, Fauzan; Khairatun Hisaaniah (At-Taujih: Jurnal Bimbingan dan Konseling Islam, 2024)
Excessive romantic love often leads to emotional imbalance and conflicts with religious values, as in Islam, true love must be directed towards Allah and His Messenger. This study aims to analyze the Islamic counseling approach in addressing excessive love through an in-depth understanding of Qur’anic sverses. The method used in this research is a qualitative approach with a tafsir analysis from trusted sources such as Tafsir As-Sa’di and Mukhtashar, along with a qualitative narrative analysis of the Qur’an. The results of the study show that the Qur’an clearly instructs believers to prioritize love for Allah and His Messenger, and that excessive romantic love is merely a temporary worldly pleasure. Islamic counseling emphasizes the importance of balance in emotional life and promotes love for Allah as the primary solution to the problem of excessive love. In conclusion, the Islamic counseling approach based on the Qur’an is effective in providing solutions to the problem of excessive love by guiding individuals towards a balanced love that is oriented toward divine values.